Optimalisasi Halaman Facebook Sebagai Sarana Promosi dan Peningkatan Kinerja Pemasaran UMKM di Kelompok Desa Prima Bumijo - Kiki Ola; Rochmad Bayu Utomo (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to optimize the use of Facebook pages as a digital promotional tool for Micro, Small, and Medium Enterprises (MSMEs) in the Prima Bumijo Village Group, Jetis District, Yogyakarta. The main problem faced by MSMEs is the limited use of social media for product marketing, with most still relying on conventional promotional methods that are less effective in reaching potential consumers widely. This activity was carried out for one month, with an implementation method through three stages: observation to identify participants' needs and obstacles, implementation of socialization and training on creating and managing business Facebook pages, and evaluation to assess the increase in participant competency. The results of the activity showed an increase in participants' knowledge and skills in creating, managing, and utilizing Facebook pages for promotion. Thus, this activity successfully improved digital literacy and MSME marketing performance, and demonstrated that optimizing social media can be an effective strategy in supporting business sustainability in the digital economy era.